Sleep prior to and following competition in professional rugby league athletes - Driller, M.; Cupples, B. (Science and Medicine in Football, 2019)
Purpose: The importance of quality sleep for elite athletes is becoming widely recognized. However, objective studies describing the sleep patterns in the lead up to and following competition are currently limited. Methods: Nine elite male Rugby League (RL) athletes performed 3 nights of sleep monitoring on six separate occasions during the RL season. The 3 nights included the following; 1) night before the game (G-1), 2) night of the game (G), and; 3) next night after the game (G+1). Sleep monitoring was performed using wrist-actigraphy. Results: There were significant differences (p < 0.05) between nights for total sleep time during the match periods (mean h:mm; 8:38, 4:53 and 6:42 for G-1, G and G+1, respectively). This was associated with a very large reduction of total sleep time on G in comparison to both G-1 (d = - 2.36) and G+1 (d = - 1.31). Sleep efficiency was also lower on the night of a game when compared to G-1 (d = - 1.58) and G+1 (d = - 1.20). Conclusion: Following RL matches, sleep onset is later, TST and SE are reduced, and sleep patterns the following night are also affected.